Konstruksi Kecantikan Mahasiswi Pengguna Skincare Di Universitas Sebelas Maret Surakarta - Lestari, Cita Dwi; Trinugraha, Yosafat Hermawan; Yuhastina, Yuhastina (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study aims to determine whether the construction of beauty formed according to female students of the Faculty of Teacher Training and Education at Sebelas Maret University who use skincare is still the same as the general beauty myth. The research method used is qualitative research with a phenomenological approach. Data were obtained through structured interviews and field observations. Social construction regarding beauty cannot be separated from the stages that follow. These stages are the initial or first receipt of information about beauty in the family sphere (externalization), the process of receiving and comparing various information related to beauty from various environments (objectivation), such as the environment of peers, college friends, and social media, and the internalization stage, when female students are able to formulate the meaning of beauty according to their own version of various environmental influences. The results showed that beauty consists of outer and inner beauty. External beauty, such as a clean face without acne and an appearance that is able to adjust the situation, While inner beauty is manifested by friendly behavior, treating others well, and good communication skills with broad insight, The meaning of beauty is influenced by internal and external factors.